2020
DOI: 10.1186/s12906-020-02899-3
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture techniques for COPD: a systematic review

Abstract: Background This is the second part of a large spectrum systematic review which aims to identify and assess the evidence for the efficacy of non-pharmacological acupuncture techniques in the treatment of chronic obstructive pulmonary disease (COPD). The results of all techniques except for filiform needle are described in this publication. Methods Eleven different databases were screened for randomised controlled trials up to June 2019. Authors in pairs extracted the data and assessed the risk of bias independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Several meta-analyses of AT treatment for COPD have been previously performed. [ 57 – 61 ] However, our study has some differences and advantages over them. Our study has the largest sample size (28 trials, 2130 participants), thus improving the statistical power.…”
Section: Discussionmentioning
confidence: 98%
“…Several meta-analyses of AT treatment for COPD have been previously performed. [ 57 – 61 ] However, our study has some differences and advantages over them. Our study has the largest sample size (28 trials, 2130 participants), thus improving the statistical power.…”
Section: Discussionmentioning
confidence: 98%
“…Fernández-Jané et al indicated that in stable COPD patients, filiform needle acupuncture added to usual treatment improved dyspnea, HRQL, and exercise capacity (42). Fernández-Jané also suggested that acupressure could improve dyspnea, HRQL, and anxiety in patients with stable COPD (43). These meta-analysis studies revealed the effectiveness of acupuncture therapy, specifically A and AM, in treating patients with COPD.…”
Section: Discussionmentioning
confidence: 98%
“…The underlying mechanisms of acupuncture on breathlessness have been covered in previous studies. [17][18][19] Acupuncture may target various aspects of the pathological process of breathlessness such as central role of endogenous opioid peptide release, 20 anti-inflammatory effect of epinephrine corticosteroid release 21 and psychological effects. 22 Why it is important to perform this review Nowadays, there is no approved therapy to control breathlessness in advanced cancer.…”
Section: How the Intervention Might Workmentioning
confidence: 99%